2008
DOI: 10.1111/j.1442-200x.2008.02547.x
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of Kawasaki disease in patients with cervical lymphadenopathy

Abstract: KDL indices may be helpful in discriminating KDL from lymphadenitis at admission. It is important to monitor the symptoms of KD in a patient with three or four KDL indices at admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 10 publications
3
37
0
Order By: Relevance
“…1, 9, 10 A Japanese comparison of 14 patients with NFKD and 24 patients with BCL 12 revealed that patients with NFKD, as in our study, were older and had higher CRP levels. In contrast, their patients with NFKD had higher WBC, ANC, and aspartate aminotransferase levels and lacked the relative anemia and thrombocytopenia which we observed.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…1, 9, 10 A Japanese comparison of 14 patients with NFKD and 24 patients with BCL 12 revealed that patients with NFKD, as in our study, were older and had higher CRP levels. In contrast, their patients with NFKD had higher WBC, ANC, and aspartate aminotransferase levels and lacked the relative anemia and thrombocytopenia which we observed.…”
Section: Discussionsupporting
confidence: 60%
“…1 Others report a high frequency of multiple enlarged nodes in both patients with NFKD and patients with BCL. 12 Patients with KD with the CT finding of retropharyngeal edema have greater extension of inflammation into deep neck spaces and more adjacent soft tissue involvement than patients with retropharyngeal edema of infectious etiology. 11 Nonetheless, patients with NFKD with retropharyngeal edema commonly experience delayed diagnosis due to the erroneous diagnosis of bacterial infection.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…One observational study found that among patients with only fever and cervical lymphadenopathy at admission, age ≥5.0 years, neutrophil count ≥10 × 10 9 /l, C-reactive protein ≥7.0 mg/dl and aspartate aminotransferase ≥30 iu/l were predictive of Kd rather than bacterial infection. 22 Patients with these findings need special attention.…”
Section: Discussionmentioning
confidence: 96%